2020
DOI: 10.48550/arxiv.2005.00918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Langevin Simulations of the Half-Filled Cubic Holstein Model

B. Cohen-Stead,
Kipton Barros,
Zi Yang Meng
et al.

Abstract: Over the past several years, reliable Quantum Monte Carlo results for the charge density wave transition temperature T cdw of the half-filled two dimensional Holstein model in square and honeycomb lattices have become available for the first time. Exploiting the further development of numerical methodology, here we present results in three dimensions, which are made possible through the use of Langevin evolution of the quantum phonon degrees of freedom. In addition to determining T cdw from the scaling of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Since our estimates of T sc lie below this upper bound, this suggests it may be possible to increase the transition temperature by increasing λ D . Recently, a QMC method based on Langevin updates of the phonon degrees of freedom [53,54] has also made studies of the cubic Holstein model amenable to simulation, and it has been found that T cdw at half-filling is increased roughly by a factor of two compared to various two-dimensional geometries [55]. We anticipate that in future studies of the 3D Holstein model one might similarly expect higher values of T sc away from half-filling, since the model will exhibit a more robust transition to long-ranged superconducting order, in contrast with the KT transition in two dimensions observed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Since our estimates of T sc lie below this upper bound, this suggests it may be possible to increase the transition temperature by increasing λ D . Recently, a QMC method based on Langevin updates of the phonon degrees of freedom [53,54] has also made studies of the cubic Holstein model amenable to simulation, and it has been found that T cdw at half-filling is increased roughly by a factor of two compared to various two-dimensional geometries [55]. We anticipate that in future studies of the 3D Holstein model one might similarly expect higher values of T sc away from half-filling, since the model will exhibit a more robust transition to long-ranged superconducting order, in contrast with the KT transition in two dimensions observed in this work.…”
Section: Discussionmentioning
confidence: 99%